The Protein Information Management System (PiMS): a generic tool for any structural biology research laboratory - Morris, C; Pajon, A; Griffiths, S; Daniel, E; Savitsky, M; Lin, B; Diprose, J; Wilter da Silva, A; Pilicheva, K; Troshin, P; van Niekerk, J; Isaacs, N; et al. (International Union of Crystallography, 2011)
The techniques used in protein production and structural biology have been developing rapidly, but techniques for recording the laboratory information produced have not kept pace. One approach is the development of laboratory information-management systems (LIMS), which typically use a relational database schema to model and store results from a laboratory workflow. The underlying philosophy and implementation of the Protein Information Management System (PiMS), a LIMS development specifically targeted at the flexible and unpredictable workflows of protein-production research laboratories of all scales, is described. PiMS is a web-based Java application that uses either Postgres or Oracle as the underlying relational database-management system. PiMS is available under a free licence to all academic laboratories either for local installation or for use as a managed service.